2017
DOI: 10.3892/mmr.2017.7934
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of ulinastatin against isoproterenol-induced chronic heart failure through the PI3K‑Akt, p38 MAPK and NF-κB pathways

Abstract: The purpose of the present study was to evaluate the cardioprotective effect of ulinastatin against isoproterenol‑induced chronic heart failure (CHF). Compared with the control group, treatment with ulinastatin decreased interventricular septal thickness and left ventricular posterior wall thickness, and improved the left ventricular ejection fraction, left ventricular fractional shortening and peak E and peak A ratio in the isoproterenol‑induced CHF rat. In addition, ulinastatin suppressed inflammation, oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Li et al reported that ulinastatin against ISO-induced chronic heart failure through the PI3 K Akt, p38 MAPK, and NF-kB pathways. 73 In this study, the ZBN treatment prevented the mRNA expression pattern of AKT signaling molecules. Similarly, the ZBN treatment modulates mTOR/PI3K/AKT signaling events in colon cancer cells.…”
Section: Discussionmentioning
confidence: 61%
“…Li et al reported that ulinastatin against ISO-induced chronic heart failure through the PI3 K Akt, p38 MAPK, and NF-kB pathways. 73 In this study, the ZBN treatment prevented the mRNA expression pattern of AKT signaling molecules. Similarly, the ZBN treatment modulates mTOR/PI3K/AKT signaling events in colon cancer cells.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, population‐based studies reiterated that there is a positive association between type 1 diabetes and HF (Miki, Yuda, Kouzu, & Miura, ). ISO treatment induced the cardiac hypertrophy (CH) as evidenced by arrhythmias, myocyte loss, and fibrosis with progression to HF (Li, Hao, Jiang, Li, & Sen, ). The current antidiabetic drugs are less effective and even harmful to patients with DM with HF.…”
Section: Discussionmentioning
confidence: 99%
“…ISO treatment induced the cardiac hypertrophy (CH) as evidenced by arrhythmias, myocyte loss, and fibrosis with progression to HF (Li, Hao, Jiang, Li, & Sen, 2018). The current antidiabetic drugs are less effective and even harmful to patients with DM with HF.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway is a highly conserved module that is involved in the majority of cellular functions, including cell proliferation, differentiation, and migration. Previous studies have shown that downregulation of the MAPK signaling pathway has a cardioprotective effect against HF (Li et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, high RAAS activity can result in apoptosis, while inhibiting RAAS can prevent apoptosis (Velez Rueda et al, 2012; Kooptiwut et al, 2015). Based on the literature, downregulating the MAPK signaling pathway can have cardioprotective effects against HF (Li et al, 2018), while inhibiting RAAS can abrogate MAPK activation (Lebeche et al, 2001).…”
Section: Resultsmentioning
confidence: 99%